Tingkat Stres Hubungannya dengan Kejadian Obesitas Penderita Hipertensi - Dian Anisia Widyaningrum; Kuswanto Kuswanto; Dika Lukitaningtyas (Pusat Riset dan Inovasi Nasional, 2025)
Excessive stress and obesity are factors that cause hypertension that are often not realized, poor psychological conditions and lifestyle patterns that are full of stressors will risk the impact of hypertension problems, if left untreated this disease can interfere with the function of other organs, such as the heart and kidneys. This study aims to determine whether stress levels are related to the incidence of obesity in people with hypertension. This study used a cross-sectional bivariate analysis method with a chi-square statistical test (Contingency Coefficient) with a sample of 55 respondents, the sampling technique used purposive sampling with the criteria of respondents who suffered from hypertension. The results showed that the stress level of most respondents experienced moderate stress as many as 28 people (50.9%) and most were obese as many as 34 people (61.8%). There is a relationship between stress levels and the incidence of obesity in people with hypertension with a p-value = 0.003 <α = 0.05. This condition can be followed up with efforts by health workers to provide education to people with hypertension in managing stress, dealing with emotions, and maintaining mental health as well as diet and exercise in achieving sustainable weight control. Thus, when stress and obesity are well managed, it will reduce the risk of hypertension recurrence in respondents.